Malware Classification For Cyber Physical System (CPS) Based On Phylogenetics - Madihah Mohd Saudi; Azuan Ahmad; Sazali Sukardi,; Noor Azwa Azreen Abd Aziz,; Muhammad ‘Afif Husainiamer (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by Scopus